Analisis Faktor yang Mempengaruhi Keputusan Pembelian Produk Kopi Kapal Api Sachet di Kota Denpasar - Novratena, Dhea; Hartiati, Amna; Yoga, I Wayan Gede Sedana (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 1 (2021): MaretDO - 10.24843/JRMA.2021.v09.i01.p15, 2021)
The purpose of this research to determine the factors that consider consumers in making purchasing decisions for Kapal Api Sachet Coffee in Denpasar and determine the dominant variables in purchasing decisions for Kapal Api Sachet Coffee.This research uses factor analysis method and data technique which is done by google form through social media, 200 questionnaires to respondents in Denpasar and 30 questionnaires in Badung Regency for validity and reliability test. The results of the analysis formed are 5 factors, namely psychological factors consisting of 10 variables with an eigenvalue of 8.891. Promotion factors are 5 variables with a total eigen value of 1.930. Product factor consists of  4 variables with a total eigenvalue of 1.779. Location factor consists of  3 variables with a total eigenvalue of 1.338. Price factor consists of  2 variables with an eigenvalue value of 1.244.  When viewed from the value of the loading factor that influences consumer decisions in purchasing Kapal Api Coffee, it is in the location factor, which is available at street vendors with a loading factor value of 0.862 and available at small shops  with a loading factor value of 0.799 . Keywords: Factor Analysis, Purchasing Decision, Marketing, Coffee